Network pharmacology combined with bioinformatics to investigate the mechanism of Xianlinggubao capsule in the treatment of osteoporosis - Yuyun Li; Rang Li; Zhanwei Zeng; Siyan Li; Shiyi Liao; Wenhui Ma; Chenhui Zhou; Daohua Xu (Phytomedicine Plus, 2021)
Background: Xianlinggubao capsule (XLGB), a traditional Chinese medicine (TCM) prescription, has been widely applied to treat osteoporosis (OP) in China. However, its active components and mechanism have not been fully elucidated. Purpose: This study aims to elucidate the active components of XLGB and its mechanism for the treatment of OP. Methods: Network pharmacology and bioinformatics are combined to elucidate the active components and mechanism of XLGB in the treatment of OP, including the acquisition of differentially expressed genes (DEGs) of OP, screening of active components and their targets of XLGB, construction of the drug-target-disease regulatory network, and analysis of the key subnetwork. Finally, these predicted results were validated by in vitro experiments and literature comparison. Results: By using bioinformatics, 2473 DEGs of OP were identified in the GEO datasets analysis (GSE35958). By using network analysis, 180 active compounds in the six herbs of XLGB and 61 OP-related targets were identified, which were significantly enriched in 118 signaling pathways and 108 GO terms. The in vitro studies showed that quercetin, luteolin, apigenin and ursolic acid, the active components of XLGB, could effectively promote the mineralization of MC3T3-E1 cells, and the combined application of ursolic acid and luteolin could significantly increase the mRNA and protein expression level of Runx2, OPN and Col l, and enhance the phosphorylation of p38 and JNK. Conclusion: XLGB plays an anti-osteoporosis role in a multi-component, multi-target and multi-pathway manner. The combination of network pharmacology and bioinformatics provides a method for the study of TCM in the treatment of complex diseases.